Norway : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2013)
This paper focuses on Norway's 2013 Article IV Consultation on economic policies to enhance long-term competitiveness. The success of the oil sector has created new competitiveness challenges. The IMF report states that rapid increases in oil wealth are also adding further pressures on the economy despite sound oil revenue management anchored by a fiscal rule. It also highlights that a slower rate of spending could better align the expected fiscal transfers with the expected long run aging- related costs that peak only after oil production is largely over.